Towards a quantitative measure of verbal effectiveness and efficiency in the Amsterdam-Nijmegen Everyday Language Test (ANELT) - Ruiter, Marina B.; Kolk, Herman H. J.; Rietveld, Toni C. M.; Dijkstra, Nienke; Lotgering, Erica (Aphasiology, 2011)
Background: A well-known test for measuring verbal adequacy (i.e., verbal effectiveness) in mildly impaired aphasic speakers is the Amsterdam-Nijmegen Everyday Language Test (ANELT; Blomert, Koster, & Kean, 1995 ). Aphasia therapy practitioners score verbal adequacy qualitatively when they administer the ANELT to their aphasic clients in clinical practice. Aims: The current study investigated whether the construct validity of the ANELT could be further improved by substituting the qualitative score by a quantitative one, which takes the number of essential information units into account. The new quantitative measure could have the following advantages: the ability to derive a quantitative score of verbal efficiency, as well as improved sensitivity to detect changes in functional communication over time. Methods & Procedures: The current study systematically compared a new quantitative measure of verbal effectiveness with the current ANELT Comprehensibility scale, which is based on qualitative judgements. A total of 30 speakers of Dutch participated: 20 non-aphasic speakers and 10 aphasic patients with predominantly expressive disturbances. Outcomes & Results: Although our findings need to be replicated in a larger group of aphasic speakers, the main results suggest that the new quantitative measure of verbal effectiveness is more sensitive to detect change in verbal effectiveness over time. What is more, it can be used to derive a measure of verbal efficiency. Conclusions: The fact that both verbal effectiveness and verbal efficiency can be reliably as well as validly measured in the ANELT is of relevance to clinicians. It allows them to obtain a more complete picture of aphasic speakers' functional communication skills.